2005
DOI: 10.1021/np050060o
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Vittaria anguste-elongata and Their Biological Activities

Abstract: Twelve new compounds, vittarin-A (1), -B (2), -C (3), -D (4), -E (5), -F (6), 3-O-acetylniduloic acid (7), ethyl 3-O-acetylniduloate (8), methyl 4-O-coumaroylquinate (9), vittarilide-A (10), and -B (11), and vittariflavone (12), as well as 20 known compounds have been isolated from the whole plant of Vittaria anguste-elongata. The structures of these compounds were determined by spectroscopic and chemical transformation methods. 5,7-Dihydroxy-3',4',5'-trimethoxyflavone (18) displayed moderate cytotoxicity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Acyclic bis [bibenzyls] are naturally occurring stilbenoids found in liverworts [7 -9], ferns [10] [11], Moraceae [12] [13], and Orichidaceae [14] [15]. This family of natural molecules has exhibited anticancer [16], antioxidant [17], antiplatelet [18], and tyrosinase inhibitory [11] activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acyclic bis [bibenzyls] are naturally occurring stilbenoids found in liverworts [7 -9], ferns [10] [11], Moraceae [12] [13], and Orichidaceae [14] [15]. This family of natural molecules has exhibited anticancer [16], antioxidant [17], antiplatelet [18], and tyrosinase inhibitory [11] activities.…”
mentioning
confidence: 99%
“…Thus, compound 1 was established as 6,6'-bis[2-(4-hydroxyphenyl)ethyl]-1,1'-biphenyl-2,2',4,4'-tetraol or 14 -14'-diDR. Compound 1 is an acyclic bis[bibenzyl] of the plagilin type [13] [23].…”
mentioning
confidence: 99%
“…The structures of the new compounds 3′,4′-dihydroxy-(3′′,4′′-dihydro-3′′-hydroxy-4′′-acetoxy)-2′′,2′′-dimethylpyrano-(5′′,6′′:7,8)-flavone-3- O - β -D-gulcopyranoside ( 1 ) and 3,3′,4′-trihydroxy-(3′′,4′′-dihydro-3′′,4′′-dihydroxy)-2′′,2′′-dimethylpyrano-(5′′,6′′:7,8)-flavone ( 2 ) were elucidated by means of spectroscopic tools and the known compounds were identified as cynaroside ( 3 ) [18], Apigetrin ( 4 ) [19], centaureidin ( 5 ) [20, 21], oroxylin A ( 6 ) [22, 23], 5,7-dihydroxy-3′,4′,5′-trimethoxyflavone ( 7 ) [24, 25], atalantoflavone ( 8 ) [26], 5-hydroxy-3′,4′,8-trimethoxy-2′′,2′′-dimethylpyrano (5′′,6′′:6,7)-flavone ( 9 ) [27, 28], and 3′,4′,5,8-tetramethoxy-2′′,2′′-dimethylpyrano (5′′,6′′:6,7)-flavone ( 10 ) [27, 28]. …”
Section: Resultsmentioning
confidence: 99%
“…Pei-Lin Wu et al isolated a compound vittarilide-A from Vittaria anguste-elongata with similar structure as 1 except that the substituting groups of C-3 and 3 0 in vittarilide-A are hydroxyls, 7 and its 13 C NMR spectral data were similar to those of 1 except for C-3 (Table 1) Since the correlation of H-6 with C-9 0 was observed in the HMBC spectrum, the feruloyl should be connected to C-6 ( Figure 2). According to the molecular formula, it is concluded that there is an ZNH 2 group in 2, and IR spectrum showed the absorption for a primary amide group; therefore, 2 was determined as 6-O-feruloyl-3-methoxy-2,4,5-trihydroxycaproylamine, named as amurenamide A.…”
Section: Resultsmentioning
confidence: 99%